Layering and shear properties of an ionic liquid, 1-ethyl-3-methylimidazolium ethylsulfate, confined to nano-films between mica surfaces. - Perkin, S; Albrecht, T; Klein, J (2010)
We report high-resolution measurements of the forces between two atomically smooth solid surfaces across a film of 1-ethyl-3-methylimidazolium ethylsulfate ionic liquid, for film thickness down to a single ion diameter. For films thinner than approximately 2 nm oscillatory structural forces are observed as the surface separation decreases and pairs of ion layers are squeezed out of the film. Strikingly, measurements of the shear stress of the ionic liquid film reveal low friction coefficients which are 1-2 orders of magnitude smaller than for analogous films of non-polar molecular liquids, including standard hydrocarbon lubricants, up to ca. 1 MPa pressure. We attribute this to the geometric and charge characteristics of the ionic liquid: the irregular shapes of the ions lead to a low shear stress, while the strong coulombic interactions between the ions and the charged confining surfaces lead to a robust film which is maintained between the shearing surfaces when pressure is applied across the film.